The mind and its Depths - Wollheim, Richard (Cambridge Harvard university press, 1993)
The mind as it is manifested in philosophy and art, in the moral life and psychoanalysis, has always been at the core of Richard Wollheim's celebrated work. This book brings together Wollheim's broad and abiding concerns to illuminate human thought at its furthest reaches of introspection and expression. Interweaving philosophy, psychoanalysis, and aesthetics, these essays reveal the critical connections between ideas and disciplines too often regarded as separate